RELIGIUSITAS DAN KONSEP DIRI DENGAN TINGKAT KENAKALAN REMAJA DIKABUPATEN PEMALANG - Fitri Awan Arif Firmansyah; Amelia Putri Nirmala; Kharisma Nawang Sigit (Universitas Pahlawan Tuanku Tambusai, 2022)
Adolescence is a period of transition from children to adulthood, a period in which individuals experience rapid growth in all fields, they are no longer children in terms of physical form, attitude, way of thinking and acting. But neither are mature adults. This period starts at approximately 13 years of age and ends approximately at the age of 21. During adolescence, children begin to be active and full of energy. Excessive energy causes teenagers to do negative things, such as grabbing, fighting, showing off physical strength and doing things that violate laws and social norms, and are difficult to regulate. This is what causes potential teenagers to carry out various behaviors that can be categorized as juvenile delinquency. At this time the turmoil of his youth was rising. The desire to find identity and get recognition from family and environment is high. Sometimes to get recognition from their environment, teenagers do things that are outside of ethics and rules. This research method uses quantitative research methods with a sample group of teenagers in Pekalongan Regency. The results obtained from this study are based on the results of data analysis showing that the major hypothesis proposed is accepted, namely that there is a relationship between self-concept and religiosity with juvenile delinquency in Pekalongan Regency. The magnitude of the influence of self-concept and religiosity with juvenile delinquency, can be seen in the effective contribution of 0.2% and 0.1%, in addition to the minor hypothesis test one proposed is accepted, namely that there is a negative relationship between self-concept and juvenile delinquency with an effective contribution. by 0.2%. While the two minor hypothesis tests that were proposed showed that they were accepted, namely that there was a positive relationship between religiosity and juvenile delinquency, with an effective contribution of 0.1%. Keywords: Self-concept, religiosity, juvenile delinquency